Chapter 1 Samhandling Under Risk (SUR) Theoretical Foundation as a Common Frame of Reference - Torgersen, Glenn-Egil (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2018)
"The main objective of this chapter is to clarify some key and overall theoretical and conceptual frameworks underlying the research project "Samhandling Under Risk" (SUR), as discussed in the various chapters of this anthology. The overall research question is: What are the basic structures of the concept of samhandling under risk and how can samhandling be created when the conditions are unpredictable? This chapter explains in particular the terms "samhandling" (SAM), "the Unforeseen" (UN), "Risk" and "SUR structures". Furthermore, these concepts are explored more deeply in relation to each other, which also frames the main approach of the anthology. As a basis, a specific understanding of "The Nature of the Unforeseen", an expanded and customized Bow-tie Model, as well as a clarification of the boundaries enclosing the research field are compared to traditional risk analysis and training in what is already known and in dealing with probable threats. Although the individual studies reported in this anthology also have their own specific angles regarding these concepts and models, they have nevertheless been based on these. The core focus is also on learning in the light of organizational learning and SUR. The boundaries, challenges and the anthology's focus on learning are also expressed in the more general and overall question: How can we as a society prepare ourselves for the unforeseen, the events and threats at the outer reaches of what we have trained for? A more indepth explanation about the background of this research project is also given in the preface of the anthology."